1985
DOI: 10.1139/x85-067
|View full text |Cite
|
Sign up to set email alerts
|

Physiological ecology of lodgepole pine (Pinuscontorta) in an enriched CO2 environment

Abstract: Relatively little work has been done to evaluate the effects of chronically high levels of carbon dioxide on growth and physiology of woody plants. In this study, seedlings of lodgepole pine (Pinuscontorta Dougl. var. latifoliaEngelm.) were grown for 5-month periods at 330, 1000, or 2000 μL CO2•L−1. Height growth; leaf area production; biomass of leaves, stems, and roots; and photosynthetic responses to changing light, moisture, and CO2 concentration were measured. Significant differences between treatments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Beadle et al (1979) observed that stomatal response to short term increases in Ca depended on the degree of existing water stress (see below). Higginbotham et al (1985) observed no CO2 related change in gs of Pinus contorta foliage grown at Ca'S as high as 2,000 #mol mol -1, while Nijs et al (1988) report that in L. perenne grown at elevated Ca, E, and presumably g~, increased with increasing Ca.…”
Section: Stomatal Responsementioning
confidence: 95%
See 4 more Smart Citations
“…Beadle et al (1979) observed that stomatal response to short term increases in Ca depended on the degree of existing water stress (see below). Higginbotham et al (1985) observed no CO2 related change in gs of Pinus contorta foliage grown at Ca'S as high as 2,000 #mol mol -1, while Nijs et al (1988) report that in L. perenne grown at elevated Ca, E, and presumably g~, increased with increasing Ca.…”
Section: Stomatal Responsementioning
confidence: 95%
“…These chambers can be placed outdoors to take advantage of natural light and temperature regimes (Jones et al 1984;Rogers et al 1984;Idso et al 1987;Szarek et al 1987), or closed chambers placed in greenhouses, where environmental factors are more readily controlled (Khan & Madsen 1986;Reekie & Bazzaz 1989;Arnone & Gordon 1990). Controlled environment rooms are frequently used to grow seedlings at enhanced Ca (e.g., Higginbotham 1985;Wray & Strain 1986). Growing conditions generally span normal terrestrial light and temperature ranges, but include Ca'S ranging from 350 to 675 #mol mol-1 (Oberbauer et al 1985;Idso 1988;Marks & Strain 1989;Nijs etal.…”
Section: Plant Culturementioning
confidence: 99%
See 3 more Smart Citations